Sosialisasi Pembuatan Media Pembelajaran Scramble untuk Meningkatkan Kualitas Pembelajaran Guru SD Negeri 1 Kualasimpang - Warsinah Warsinah; Patri Janson Silaban; Lasma Silaban (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Education is one of the important pillars in nation development. The quality of education is largely determined by the quality of teachers. Quality teachers are able to create an effective and enjoyable learning process for students. One of the factors that supports the quality of learning is the use of interesting and interactive learning media. Scramble learning media is an interesting and interactive learning media. This socialization aims to provide knowledge and skills to SD Negeri 1 Kualasimpang teachers in creating interesting and interactive Scramble learning media. The results of the activity showed that the teachers were very enthusiastic in participating in the socialization and gaining new knowledge and skills in creating Scramble learning media. It is hoped that with this activity, SD Negeri 1 Kualasimpang teachers can apply Scramble learning media in the classroom learning process, so that they can improve the quality of learning and student motivation.